2016
DOI: 10.1002/hed.24418
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear protein in testis midline carcinoma of larynx: An underdiagnosed entity

Abstract: Absence of well-known risk factors, pathologic finding of lack of mucosal involvement and lack of squamous differentiation with poorly differentiated carcinoma, should prompt clinicians to consider this rare entity as a possible diagnosis. © 2016 Wiley Periodicals, Inc. Head Neck 38:E2471-E2474, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…13 Due to the availability of the antibody to NUT, a protein which is normally exclusive to the testes and diagnostic of NMC for outside F I G U R E 3 (A) Program of intensity-modulated radiation therapy; (B) Neck magnetic resonance imaging examination 15 mo after vocal cord resected expression, the diagnosis of NMC is more convenient and frequent. 14 However, the laryngeal NMC is still extremely rare with only seven cases reported till now, 3,6 and we added one new case of our own. There were four males and four females and the mean age of diagnosis is 26.6 years (Table 1), which is in accordance with the young age (avg.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…13 Due to the availability of the antibody to NUT, a protein which is normally exclusive to the testes and diagnostic of NMC for outside F I G U R E 3 (A) Program of intensity-modulated radiation therapy; (B) Neck magnetic resonance imaging examination 15 mo after vocal cord resected expression, the diagnosis of NMC is more convenient and frequent. 14 However, the laryngeal NMC is still extremely rare with only seven cases reported till now, 3,6 and we added one new case of our own. There were four males and four females and the mean age of diagnosis is 26.6 years (Table 1), which is in accordance with the young age (avg.…”
Section: Discussionmentioning
confidence: 69%
“…However, the laryngeal NMC is still extremely rare with only seven cases reported till now, and we added one new case of our own. There were four males and four females and the mean age of diagnosis is 26.6 years (Table ), which is in accordance with the young age (avg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since initial report in 1991, total 105 cases were described. 5,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The sinonasal tract accounted for 73.4% of initial presenting site and followed by salivary gland (11%), larynx (7.3%), pharynx (4,6%), and oral cavity (3.7%) ( Table 3). Regarding the overall frequency of NUT carcinoma in head and neck, previous studies reported different results according to the study subjects (1.9-17.9%).…”
Section: Frequency and Distribution Of Nc With Review Of Literaturementioning
confidence: 99%
“…The encoded oncoprotein BRD4–NUT contributes to carcinogenesis by blocking epithelial cell differentiation and drives growth of the NMC cells . Although recognized only recently, a series of publications since 2001 have established the concept of NUT NMC as a distinct entity …”
Section: Introductionmentioning
confidence: 99%